Bidirectional relationships between older Singaporeans' social networks and health outcomes: a cross-lagged panel analysis - Nathan Widjaja (Nanyang Technological University, 2024)
While growing research has found social networks to be broadly beneficial for older adults’ health outcomes, we know little about whether friend and family networks have differing impacts on health, as well as how older adults’ health statuses might conversely influence their social networks over time. Using three waves of data (2009; 2011-12; 2015) from a nationally representative sample of Singaporeans aged 60 and above (n = 1,367), this study uses cross-lagged analyses to investigate the bidirectional relationships between older adults’ family and friend networks and their mental and functional health outcomes. Across all waves, I find that greater depressive symptomology predicted both lower future friend and family network scores, while only family network scores predicted lower future depressive symptomology. These results reinforce the centrality of family ties for Singaporean older adults’ mental health and highlight the need for more targeted medical-social interventions for older adults with poorer mental health.